Rat Mesenchymal Stromal Cell Sheets Suppress Renal Fibrosis via Microvascular Protection. (1st November 2019) - Imafuku, Aya; Oka, Masatoshi; Miyabe, Yoei; Sekiya, Sachiko; Nitta, Kosaku; Shimizu, Tatsuya
Abstract: Renal fibrosis is one of the largest global health care problems, and microvascular (MV) injury is important in the development of progressive fibrosis. Although conventional cell therapy suppresses kidney injury via the role of vasoprotective cytokines, the effects are limited due to low retention of administered cells. We recently described that transplantation of hepatocyte growth factor (HGF)-transgenic mesothelial cell sheets showed a remarkable cell survival and strong therapeutic effects in a rat renal fibrosis model. Due to the translational hurdles of transgenic cells, we here applied this technique for allogeneic transplantation using rat bone marrow mesenchymal stromal cells (MSCs). MSC sheets were transplanted onto the kidney surface of a rat renal ischemia–reperfusion-injury model and the effects were compared between those in untreated rats and those receiving intravenous (IV) administration of the cells. We found that donor-cell survival was superior in the cell sheet group relative to the IV group, and that the cell sheets secreted HGF and vascular endothelial growth factor (VEGF) up to day 14. Transplantation of cell sheets increased the expression of activated HGF/VEGF receptors in the kidney. There was no evidence of migration of transplanted cells into the kidney parenchyma. Additionally, the cell sheets significantly suppressed renal dysfunction, MV injury, and fibrosis as compared with that observed in the untreated and IV groups. Furthermore, we demonstrated that the MSC sheet protected MV density in the whole kidney according to three-dimensional microcomputed tomography. In conclusion, MSC sheets strongly prevented renal fibrosis via MV protection, suggesting that this strategy represents a potential novel therapy for various kidney diseases. Stem Cells Translational Medicine 2019;8:1330&1341 : Abstract : Rat bone marrow mesenchymal stromal cell sheets were transplanted onto the kidney surface. In ischemia–reperfusion-injury, microvascular density loss caused by endothelial injury resulted in progressive renal fibrosis. Mesenchymal stromal cell sheets remained long-term on the kidney surface and protected the microvasculature, which resulted in suppression of progressive fibrosis. The therapeutic effects were partially explained by the role of hepatocyte growth factor/vascular endothelial growth factor secreted from mesenchymal stromal cell sheets.